2021
DOI: 10.1039/d1bm00616a
|View full text |Cite
|
Sign up to set email alerts
|

18F-Labeled magnetic nanovectors for bimodal cellular imaging

Abstract: Surface modification of nanocarriers enables selective attachment to specific molecular targets within a complex biological environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…25 Radiolabeling of the Fe 3 O 4 MNPs is a common method for monitoring the distribution of the nanoparticles in-vivo. 20,21 We have carried out radiolabeling of PPNMs with 64 Cu 2+ and 177 Lu 3+ (Scheme 2) by exploiting the high coordinative affinity of polyphosphate moieties of PPNMs towards metal ions as a driving force for radiolabeling. It is noteworthy to mention that these polyphosphate moieties capture 64 Cu 2+ and 177 Lu 3+ ions from solution by forming chelate complexes like those of carboxylate ions towards metal ions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Radiolabeling of the Fe 3 O 4 MNPs is a common method for monitoring the distribution of the nanoparticles in-vivo. 20,21 We have carried out radiolabeling of PPNMs with 64 Cu 2+ and 177 Lu 3+ (Scheme 2) by exploiting the high coordinative affinity of polyphosphate moieties of PPNMs towards metal ions as a driving force for radiolabeling. It is noteworthy to mention that these polyphosphate moieties capture 64 Cu 2+ and 177 Lu 3+ ions from solution by forming chelate complexes like those of carboxylate ions towards metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, the labelling of MNPs with suitable radionuclides is an advanced technique for biodistribution studies as well as their in-vivo tracking using various multimodal imaging techniques. 20,21 Herein, we have prepared negatively charged polyphosphate grafted Fe 3 O 4 nanomagnets (PPNMs), and explored their efficacy for intracellular delivery of anticancer drug, gemcitabine hydrochloride (GEM) through electrostatic interaction. These nanocarriers are highly dispersible in physiological medium, and GEM loaded PPNMs (GEM-PPNMs) exhibited pH dependent drug release characteristics, substantial cellular uptake and higher toxicity to human lung cancer (A549) and breast cancer (MCF-7) cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is particularly important in the context of radiopharmaceutical chemistry, as avoiding the presence of even trace organic solvents in clinical doses is vital . This water compatibility has also allowed for the radiolabeling of live cells, sensitive proteins, , nanoparticles, metal–organic frameworks, and liposomes . While concerns about the biocompatibility of the Cu­(I) cation have long hampered the use of the CuAAC reaction with biomolecules, the advent of catalysts bearing water-soluble Cu­(I)-stabilizing ligands like tris­(3-hydroxypropyltriazolylmethyl)­amine (THPTA) can ameliorate these worries by protecting sensitive biomolecules from hydrolysis or oxidative damage due to free Cu cations. , …”
Section: The Copper-catalyzed Azide–alkyne Cycloadditionmentioning
confidence: 99%
“…However, studies have found that ordinary magnetic nanoparticles will be phagocytized by the reticuloendothelial system (RES) and distributed in various physiological barriers, , and the number of nanoparticles reaching the tumor site through passive targeting is very small. Active targeting can generally provide better uptake and intratumor enrichment; therefore, in the diagnosis and treatment based on Fe 3 O 4 nanoparticles, surface modification especially specific surface property construction design to improve the targeting capability remain a research focus. …”
Section: Introductionmentioning
confidence: 99%